The Courtesy Conversation In Daily Life - Fadila, Nazwa Rizky; Lubis, Yani; Rahma Dalimunthe, Saskia; Farhan Handoko, Muhammad; Andika, Riki Bayu (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study explores the role of conversational routines and politeness strategies in fostering effective communication across diverse cultural and professional contexts. By integrating phonological analysis and sociolinguistic perspectives, the research examines how sound structures, such as phonemes and syllable patterns, influence the production and perception of polite expressions. Data were collected through recorded conversations and analyzed using qualitative coding and phonological tools, including minimal pairs exercises and syllable segmentation. The findings reveal that conversational routines, while rooted in cultural traditions, adapt dynamically to situational demands, balancing stability with flexibility. The study also highlights the significance of politeness as a social tool, both in everyday and professional interactions, where it ensures respect and cohesion. Educational interventions using interactive media and phonological techniques were found to enhance participants’ ability to navigate routine conversations with linguistic and cultural precision. These insights contribute to a deeper understanding of the interplay between language structures and social norms, offering practical implications for language education, cross-cultural communication, and professional training. The findings underscore the importance of phonological clarity and conversational adaptability in promoting inclusivity and mutual respect in diverse interactions.